(untitled) - Haycraft, John (London, 1999)
This book is designed for those who know little or nothing about teaching english as a foreign or second language. It is, therefore, suitable pre-course reading for an RSA Preparatory Certificate, or any other form of initial training.
Keywords: English language,English language; Study and teaching,Study and teaching,Foreign speakers